The Influence of Soil Chemical Properties on Palm Oil Production (Elaeis guineensis Jacq) on Dry Acid Mineral Soil in Rokan Hulu Regency - Sri Syahputri; Afdhal; Boris Kaido; Feri Agriani; Fajar Aga Wandana (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Oil palm (Elaeis guineensis Jacq.) is one of Indonesia's leading commodities, significantly contributing to the national GDP, foreign exchange earnings, and tax revenues. As the world’s largest producer and exporter of crude palm oil (CPO), Indonesia’s palm oil industry plays a strategic role in maintaining economic stability and global competitiveness. Oil palm productivity is influenced by various factors, including soil chemical properties, particularly in mineral soils with varying fertility levels. This study aims to analyze the effect of soil chemical properties on oil palm fresh fruit bunch (FFB) production in Rokan Hulu Regency, Riau Province. The parameters analyzed include soil pH, organic matter content, cation exchange capacity (CEC), base saturation (BS), and macronutrient availability (nitrogen, phosphorus, potassium). The research methodology involves secondary data collection from plantation companies, multiple linear regression analysis, and Duncan's test to determine the effect of each soil parameter on oil palm production. The results indicate that soil chemical properties, including pH, CEC, BS, nitrogen, phosphorus, and potassium, significantly affect oil palm productivity. Optimal production was observed in soils with a pH of 4.9–6.5, high CEC (>3.8 cmol(+)/kg), and base saturation above 16.3%. The low nutrient content at the study site highlights the need for soil fertility management through liming and organic fertilizers. The study outputs include soil chemical property maps, soil-parameter-based models for predicting oil palm production, and recommendations for mineral soil management to optimize production.